Modelling Subscription‑Based Streaming Services for Books - Berglund, Karl; Tanderup Linkis, Sara (Mémoires du livre / Studies in Book Culture, 2022)
By departing from the Nordic countries, the purpose is to explain and conceptualize how subscription-based streaming services for books operate in the contemporary book trade, and furthermore to discuss what effects these new business models are causing regarding the production, distribution, and consumption of books. A model is proposed that outlines the aspects of streaming services and the relationships to other actors involved. The model illustrates how streaming services affect the entire chain of publishing, and influence the constitution of books in contemporary digital culture. Since audiobooks are by far most popular, the production get altered to suit this format. Streaming services themselves also act as publishers, which makes them powerful. Distributional aspects are both more complex and more important in streaming services than in traditional book retailing. When consumption is transferred to digital platforms, the distributional frame and the final product converge, and consumer data becomes a key source of information.